Growth And Production Of Several Rice Varieties With The Biochar From Different Sources Of Materials - Prisman perdana Hutapea; Jonatan Ginting; Nini Rahmawati (UNIVED Press, Dehasen University Bengkulu, 2022)
This research will be carried out in the experimental land of the Tanjung Morawa Seed Center, Lubuk Pakam District, Deli Serdang Regency. The purpose of this research is to find out how the growth and production of several varieties of irrigated rice with biochar from different source. The experimental design used in this study was a split plot design with 2 factors. The first factor is: The provision of various sources of biochar with 5 levels of treatment: No biochar, rice husk biochar, coconut shell biochar, oil palm empty bunch biochar and jengkol skin biochar. The second factor was: Ciherang, Hipa 19, Inpari 33. Parameters observed were plant height (cm), number of panicles, weight of 1000 grains (g and soil analysis. The results showed that the use of several varieties of lowland rice on the growth and production of irrigated rice had a significant effect on the height of rice plants from 6-9 WAP. The use of several varieties of rice such as Ciherang, Hipa 10 and Inpari 33 varieties showed differences in plant height starting at the age of 6 WAP. The results of the final analysis of paddy fields after being given biochar treatment experienced an increase in nutrients such as N-total, P, K and organic C in all treatments.